Consent, Fraud and Family Law. Issue 1 (2nd January 2016) - Diduck, Alison
Abstract: In two recent cases the Supreme Court unanimously clarified that one party's fraudulent non-disclosure of material facts 'unravels' any agreement made in their absence. Because the parties' agreement is a sine qua non of a consent order, the order may be set aside, despite the desirability in family law of clean break and certainty. Victims of fraud in matrimonial proceedings should not be left in a worse position than victims in other civil proceedings. However, while consistency across different areas of civil law was important here, are there any circumstances in which inconsistency may be justified?